The Relation Pattern Between Energy and Protein Intake Against Student's Body Mass Index: Case Study at UIN Sunan Ampel Surabaya Students - Ilham Ilham; Sarita Oktorina; Moh. Rizqi Haqiqi As'at (Journal of Health Science and Prevention, 2017)
The content of food nutrients is the key to for the body development as well maintenance. Poor food intake along with unhealthy lifestyle is one of the factors that cause various chronic diseases. Students belong to the transition age group from late adolescence to early adulthood. Most students live in boarding houses and dormitories, so students have an irregular diet and are unhealthy. The research aimed to investigate the relationship between energy and protein intake with Body Masa Index among active students at the Faculty of Science and Technology. The result showed that there was a significant correlation between energy consumption, protein consumption and students knowledge, with student;s Body Mass Index, while 8.3% of the respondents were identified into the 1st category of obesity